9‐Year Trend in the Management of Acute Heart Failure in Japan: A Report From the National Consortium of Acute Heart Failure Registries. Issue 18 (18th September 2018) - Shiraishi, Yasuyuki; Kohsaka, Shun; Sato, Naoki; Takano, Teruo; Kitai, Takeshi; Yoshikawa, Tsutomu; Matsue, Yuya
Abstract : Background: Acute heart failure (AHF) is a heterogeneous condition, and its characteristics and management patterns differ by region. Furthermore, limited evidence is available on AHF outside of Western countries. A project by the National Consortium of Acute Heart Failure Registries was designed to evaluate the trends over time in patient backgrounds, in‐hospital management patterns, and long‐term outcomes of patients with AHF over 9 years in Japan. Methods and Results: Between 2007 and 2015, registry data for patients with AHF were collected from 3 large‐scale quality AHF registries (ATTEND/WET‐HF/REALITY‐AHF). Predefined end points were trends over time in age, sex, and clinical outcomes, including short‐ and long‐term mortality and readmission for heart failure. The final data set consisted of 9075 patients with AHF. No significant differences in patient backgrounds and laboratory findings (eg, anemia or renal function) were observed, with the exception of patient age; mean age became substantially higher over 9 years (71.6–77.0 years; P for trend, <0.001). On the contrary, length of hospital stay became shorter (mean, 26–16 days). These changes were not associated with in‐hospital mortality (4.7–7.5%) or 30‐day heart failure readmission rate (4.8–5.4%), as well as 1‐year mortality and heart failure readmission rate (20.1–23.3% and 23.6–26.2%, respectively). Conclusions: Length of hospital stay in patients with AHF shortened over the 9‐year period despite the increasing age of the patients. However, short‐ and long‐term outcomes do not seem to be affected; continuous efforts to monitor clinical outcomes in patients with AHF are needed.